2017
DOI: 10.1111/hepr.12969
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 secreted by mesenchymal stem cells attenuates acute liver failure through inhibiting pyroptosis

Abstract: Pyroptosis was inhibited after IL-10 infusion and inhibition of NLRP3 by MCC950 reversed liver dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…For example, secretion of EGF by MSCs attenuated apoptosis in podocytes 31 and IL-10 secretion by MSC ameliorated liver injury in mice. 16 Collectively, the results from these studies and our own data suggest that beyond P3, AD-MSCs may exhibit reduced potency while for BM-MSCs, culturing them to P5 might augment their potency.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, secretion of EGF by MSCs attenuated apoptosis in podocytes 31 and IL-10 secretion by MSC ameliorated liver injury in mice. 16 Collectively, the results from these studies and our own data suggest that beyond P3, AD-MSCs may exhibit reduced potency while for BM-MSCs, culturing them to P5 might augment their potency.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, BM‐MSCs secreted only two (IL‐8 and RANTES) cytokines at higher amounts at P3 compared to P1, and secretion of six cytokines and growth factors (fractalkine, PGDF‐BB, IL‐2, IL‐6, IL‐8, and RANTES) was significantly increased at P5 compared to P1. Multiple studies indicate that the biologic functions mediated by MSCs are dependent on cytokine release by the MSC . Since the cytokine secretion profiles of both AD‐MSC and BM‐MSC seem to be passage dependent, it stands to reason that MSC passage number would also influence their biological potency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, blocking IL-1 signaling by treatment with the recombinant human IL-1 receptor antagonist (IL-1ra) anakinra alleviated DGalN/LPS leaded liver injury [30,40]. Moreover, the NLRP3 inhibitor MCC950 has also shown to protect mice from chemically-induced liver injury [41,42]. Here, we found that although NLRP3 de ciency decreased serum and hepatic IL1β levels in DGalN/LPS treated mice, the liver injury is not improved, suggesting that IL1β may have a limited role in DGalN/LPS induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence showed that MSCs secretions exerted a bene cial effect by reducing the in ammatory response, promoting the survival and proliferation of injured cells, and ameliorating liver injury. (21,(44)(45)(46)(47) In the present study, microcapsules were used as carriers to encapsulate UMSCs and hepatocytes to persistently release the secretory factors contributing to the repair of impaired liver and the reduction of in ammatory response in ALF. And more, HNF4α-UMSCs signi cantly argument the therapeutic effects on ALF mice (Fig.1-5).…”
Section: Discussionmentioning
confidence: 99%